Risk Society, Global Security, Accelerated History and Uncertainty of Its Path (Kriminalističke teme, 2007)
Based on all signs of changes with which we entered into the 21 st.century, our perception of the world is changing quickly.Followed by track of modern happening and deep changes of the postmodern world, we can barely understand what informatic new age really means and all consequences that brings. World's tehnological process and its knowledge makes brand new way of communication, new type of society, and a new media and political culture. Fast changing of the world takes huge proportion, bigger than ever in human history, and that changes our reality on all levels of human existence.Modern global process makes new social paradigm which is pointing on specific complexity of our time. In our society, which is marked as risk society, unsafety grows in all fields of modern social life, and many authors see directly connection between fast technological world transformation and global unsafety.